Grounded glass as a sustainable technology in hydraulic concrete - Rojas-Ramos, Andrés (2021)
Hydraulic concrete is considered as the most consumed human-made resource; however, its elaboration implies a direct and indirect environment pollution. The hydraulic cement is one of the principal components of hydraulic concrete, which, besides to be the most expensive element of hydraulic concrete, is also the one that causes the greatest contamination in its manufacture, emitting a high amount of CO2. This article discloses some of the characteristics and benefits of using ground glass as a partial substitute for cement in hydraulic concrete, being this a promising proposal to bring the world of construction closer to sustainability. Researchers around the world have been in charge of seeking the optimization of the concrete mix considering the variables that are linked to it. Those investigations have obtained positive results, showing that this proposal implies not only environmental, but also mechanical and economic advantages.